2007
DOI: 10.1088/0022-3727/40/24/025
|View full text |Cite
|
Sign up to set email alerts
|

Ion current distribution during deposition of dielectric material using an insulating porous alumina template

Abstract: We have presented a numerical simulation of the deposition of dielectric material using an insulating porous template. A Maxwellian distribution has been used to calculate the original ion velocity when the ion leaves the plasma and enters the sheath. The microscopic electrical field over the template is considered to affect the ion motion. It is found that the electron temperature and nanopore structure can change the ion deposition rate effectively. However, the deposition rate decreases only slightly with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…We also found that the effect of the ion density on carbon loss near the nanotube base is small. Note that the ion bombardment experiments and atomistic simulations reveal that the ion bombardment in a suitable energy range allows structural defects to be healed resulting in an enhanced nucleation of the carbon nanotube cap …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We also found that the effect of the ion density on carbon loss near the nanotube base is small. Note that the ion bombardment experiments and atomistic simulations reveal that the ion bombardment in a suitable energy range allows structural defects to be healed resulting in an enhanced nucleation of the carbon nanotube cap …”
Section: Resultsmentioning
confidence: 99%
“…Note that the ion bombardment experiments and atomistic simulations reveal that the ion bombardment in a suitable energy range allows structural defects to be healed resulting in an enhanced nucleation of the carbon nanotube cap. [65][66][67][68]…”
Section: Resultsmentioning
confidence: 99%
“…In many practical applications, nanomaterials are dielectric such as nanometer‐sized ZnO dots which have exceptional excitonic properties further enhanced by quantum confinement effects and as such are particularly promising as light emitters in nanophotonic integrated circuits 5, 26–28. In i‐PVD of dielectric materials, electric charge accumulated on dielectric surfaces significantly affects the surface potential and the process throughput and precision 29. In cases, when the surface potential is low, the nanodot crystallinity can be quite poor due to lower ion energy upon collision with the substrate, which significantly compromises the product quality.…”
Section: Introductionmentioning
confidence: 99%
“…18 However, electric charge accumulated on dielectric surfaces exposed to plasmas and ion beams distorts ion/cluster trajectories and reduces the process throughput and precision. 19 This is why attempts have been made to periodically remove the accumulated charge by applying ac or pulsed voltages to bias the dielectric materials being processed, sustain the plasma, or release suitable building units. 20,21 However, it is very challenging to use this technique for treatment of such nanovoided materials.…”
mentioning
confidence: 99%